Replacing Ground Rod Joining Cable from Copper to Galvanized Iron - Prashobh, Karunakaran; Katherine, Thomas; Shirley, Rufus; Lakshmanan, Gurusamy; Abdullah Azfar, Setari (Research India Publications, 2016)
Research on electrical grounding is well established over the past 180 years but recently due to the ever increasing price of copper, theft of copper from grounding systems has become common. The cost of a lack of integrity of electrical power systems due to the stolen copper from grounding systems can be massive. Therefore it is the objective of this research is to study if the 35mm2 copper ground rod joining cable can be replaced with galvanized iron. Galvanized iron was chosen as a replacement because of its extensive used in civil engineering works which has resulted in its cheap price and easy availability. It also has sufficient electrical conductivity. The methodology of this work is to measure the ground resistance with a ground resistance meter; with copper and galvanized iron as the joining cable, over a period of eight months. The findings are that though the ground resistance using galvanized iron is higher, it is still cost effective to use more ground rods with galvanized iron joins rather than fewer ground rods with copper joints. Another unexpected finding is that beyond a certain number of joined ground rods, the reduction in ground resistance is not significant. A future work is to solve the remaining weak point in grounding systems which is the join between the joining cable and the ground rod.